Inter- and Intra-Individual Analysis of Post-Exercise Hypotension Following a Single Bout of High-Intensity Interval Exercise and Continuous Exercise: A Pilot Study - Costa, E. C.; Dantas, T. C. B.; de Farias Junior, L. F.; Frazão, D. T.; Prestes, J.; Moreira, S. R.; Ritti-Dias, R. M; Tibana, R. A.; Duhamel, T. A. (International Journal of Sports Medicine, 2016)
Recently, post-exercise blood pressure (BP) has been considered a predictive tool to identify individuals who are responsive or not to BP reductions with exercise training (i. e., “high” and “low responders”). This study aimed to analyze the inter- and intra-individual BP responsiveness following a single bout of high-intensity interval exercise (HIIE) and continuous exercise (CE) in normotensive men (n=14; 24.5±4.2 years). Mean change in BP during the 60 min period post-exercise was analyzed and minimal detectable change (MDC) was calculated to classify the subjects as “low” (no post-exercise hypotension [PEH]) and “high responders” (PEH occurrence) following each exercise protocol (inter-individual analysis). The MDC for systolic and diastolic BP was 5.8 and 7.0 mmHg. In addition, a difference equal/higher than MDC between the exercise protocols was used to define an occurrence of intra-individual variability in BP responsiveness. There were “low” and “high” PEH responders following both exercise protocols (inter-individual variability) as well as subjects who presented higher PEH following a specific exercise protocol (intra-individual variability between exercise protocols). These results were observed mainly for systolic BP. In summary, PEH is a heterogeneous physiological phenomenon and, for some subjects, seems to be exercise-protocol dependent. Further investigations are necessary to confirm our preliminary findings.
Keywords: blood pressure; exercise; post-exercise hypotension; responsiveness; variability; personalized medicine